THU0115 Psychological and functional states predict disease flare following tnf inhibitor tapering in patients with rheumatoid arthritis: a post-hoc analysis of data from the optimisingtnf tapering in ra (OPTTIRA) cohort. (12th June 2018) - Bechman, K.; Sin, F.E.; Ibrahim, F.; Norton, S.; Scott, D.; Cope, A.; Galloway, J.
Abstract : Background: Tapering or discontinuation of anti-TNF therapy appears to be feasible, safe and effective in a selected proportion of Rheumatoid Arthritis (RA) patients. Depression is highly prevalent in RA and may impact on flare incidence through a number of mechanisms. It is an independent predictor for flare in patients with active disease and is negatively associated with remission. 1 To date, there are no studies directly addressing the role of depression, anxiety or low mood in predicting flares in patients tapering their biological therapy. Objectives: To investigate if psychological and functional states predict flare in RA patients with low disease activity (LDA) or in remission who undergo treatment tapering of their anti-TNF agents. Methods: This study is a post-hoc analysis of the OPTTIRA trial, 2 a multi-centre, prospective, randomised, open label study investigating anti-TNF tapering in established RA patients in sustained LDA. Baseline patient-reported outcomes including HAQ-DI, EQ-5D, FACIT-F, and SF-36 including the Mental Health Index (MHI) component were collected. The MHI has been validated as a screening tool for depression in RA patients. 3 The primary outcome was flare, defined as an increase in DAS28 ≥0.6, and at least one additional swollen joint. Logistic regression was used to identify patient-reported outcomes that predict flare, adjusting for baseline covariates (age, gender, treatment arm, DAS28 and BMI). Results: 97 were randomised into a tapering arm, either by 33% or 66% of their anti-TNF dose. The majority of patients were on methotrexate in combination with their anti-TNF therapy (n=67, 69%) and the median disease duration was 11 years [IQR: 7–17]. Seventy three (75%) fulfilled DAS28 remission criteria (DAS28 <2.6). The median SF36 MHI score was 84. A score of ≤56, the cut off used to detect depression was observed in 11% of patients. Forty one patients (42%) flared. Baseline DAS28 score was associated with flare, remaining significant after adjusting for covariates [HR 1.96 (95% CI: 1.18, 3.24) p=0.01]. Disability (SF-36 physical component), fatigue (FACIT-F) and mental health (SF-36 MHI) predicted flare in univariate models (figure 1). In multivariate analyses, only MHI score remained a statistically significant independent predictor of flare [HR per 10 units 0.74 (95% CI: 0.60, 0.93) p=0.01]. Conclusions: Baseline DAS28 and mental health predict flare events in patients in LDA who taper their anti-TNF agents. Other psychological and functional states, measured by patient-reported outcome do predict flare events although the effect size is small and does not persist when adjusting for known predictors. Based on these findings, an assessment of functional and mental health states should be considered prior to biologic tapering. References: [1] Michelsen B, et al. Ann Rheum Dis2017;76(11):1906–1910. [2] Ibrahim F, et al. Rheumatology2017;56(11):2004–2014. Acknowledgements: Funding : The trial was funded by Arthritis Research UK (grant reference number 18813) Disclosure of Interest: None declared